The selectivity of commercial trawls in Malaysia - Mohamed, Mohd. Ibrahim
Trawls operated by commercial fishermen were tested with the covered codend method to determine its selectivity on species of fish caught. The 25mm codend retained 98.2% of fish while the 51mm codend retained 56.1% of the catch. Trash fish component of the codend was 46.7% for the smaller mesh size codend and 34.6% for the larger. Trawling speed,bottom time and catch size were found to effect the L50 of the different target species of fish. The effect of catch size in lowering mesh selection was very prominent on small mesh sized nets.